Chemical interactions and gel properties of black carp actomyosin affected by MTGase and their relationships. (1st April 2016) - Jia, Dan; Huang, Qilin; Xiong, Shanbai
Highlights: γ-carboxyamide and amino cross-links induced by MTGase built in suwari gels stage. S–S bonds were formed in both suwari and kamaboko gels to enhance gel network. Kamaboko gels had higher G′ and CL than suwari gels at same addition of MTGase. G′ was mainly determined by covalent cross-links and had positive correlation. Covalent bonds promoted CL while non-covalent bonds were in favor of water holding. Abstract: Partial least squares regression (PLSR) was applied to evaluate and correlate chemical interactions (–NH2 content, S–S bonds, four non-covalent interactions) with gel properties (dynamic rheological properties and cooking loss (CL)) of black carp actomyosin affected by microbial transglutaminase (MTGase) at suwari and kamaboko stages. The G′ and CL were significantly enhanced by MTGase and their values in kamaboko gels were higher than those in suwari gels at the same MTGase concentration. The γ-carboxyamide and amino cross-links, catalyzed by MTGase, were constructed at suwari stage and contributed to the network formation, while disulfide bonds were formed not only in suwari gels but also in kamaboko gels, further enhancing the gel network. PLSR analysis revealed that 86.6–90.3% of the variation of G′ and 91.8–94.4% of the variation of CL were best explained by chemical interactions. G′ mainly depended on covalent cross-links and gave positive correlation. CL was positively correlated with covalent cross-links, but negatively related to non-covalent bonds, indicating that covalent bonds promoted water extrusion, whereas non-covalent bonds were beneficial for water-holding.